Selective alkylation of amines with alcohols by Cp*-iridium(III) half-sandwich complexes - Wetzel, Alexander; Wöckel, Simone; Schelwies, Mathias; Brinks, Marion K.; Rominger, Frank; Hofmann, Peter; Limbach, Michael (Organic letters, 2013)
[Cp*Ir(Pro)Cl] (Pro = prolinato) was identified among a series of Cp*-iridium half-sandwich complexes as a highly reactive and selective catalyst for the alkylation of amines with alcohols. It is active under mild conditions in either toluene or water without the need for base or other additives, tolerates a wide range of alcohols and amines, and gives secondary amines in good to excellent isolated yields.
Gesehen am 04.11.2021